Islamic Education and the 4Rs of Post-Conflict Reconstruction: A Critical Integrative Review of Selected Conflict-Affected Settings in Sub-Saharan Africa - Zainal Arifin; Tri wahyudi Ramdhan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Global discourse on Islamic education in sub-Saharan Africa is often framed through a securitization lens, positioning madaris and Qur'anic schools as deradicalization objects or security threats, overlooking their standing as grassroots actors with cultural legitimacy in peacebuilding. This article examines whether, and under what conditions, Islamic educational institutions in conflict-affected settings function as legitimate peacebuilding actors. Drawing on a Critical Integrative Review of literature (2005–2026, prioritizing 2020–2026), UN field reporting, and African Union policy documents, the analysis applies the 4Rs framework (Redistribution, Recognition, Representation, Reconciliation) to evidence from Nigeria, Sudan, Somalia/Somaliland, Niger, and Cameroon. Four bounded findings emerge, each qualified by disconfirming evidence. First, faith-financed institutions appear to sustain access to basic literacy where state provision has receded, though redistributive effects are uneven and gendered. Second, value-based curricula may affirm religious identity in ways that complicate extremist alienation narratives, though reduced recruitment susceptibility is a testable hypothesis rather than a finding. Third, engaging the ulama as co-designers is associated with greater community acceptance, while narrowing the space for women and youth in some settings. Fourth, Islamic ethical traditions offer locally intelligible repertoires for reconciliation, though direct evidence of outcomes in African conflict settings remains thin. The article proposes a bounded faith-based extension of the 4Rs, conditioned on low state and high religious legitimacy, aligning policy implications with the African Union Post-Conflict Reconstruction and Development framework. Findings are context-specific, not generalized to sub-Saharan Africa as a whole.